Omics Playground: a comprehensive self-service platform for visualization, analytics and exploration of Big Omics Data. Issue 1 (6th December 2019) - Akhmedov, Murodzhon; Martinelli, Axel; Geiger, Roger; Kwee, Ivo
Abstract: As the cost of sequencing drops rapidly, the amount of 'omics data increases exponentially, making data visualization and interpretation—'tertiary' analysis a bottleneck. Specialized analytical tools requiring technical expertise are available. However, consolidated and multi-faceted tools that are easy to use for life scientists is highly needed and currently lacking. Here we present Omics Playground, a user-friendly and interactive self-service bioinformatics platform for the in-depth analysis, visualization and interpretation of transcriptomics and proteomics data. It provides a large number of different tools in which special attention has been paid to single cell data. With Omics Playground, life scientists can easily perform complex data analysis and visualization without coding, and significantly reduce the time to discovery.